(untitled) (Bangladesh Journal of Psychiatry, 2022)
Conversion disorder has several co-morbidities. Bipolar disorder is one of them. There is no definitive treatment protocol for cases like this. In this report, we presented a case of a 30-years old female who had this kind of condition. Initially, she had a presentation like conversion disorder. But after giving her treatment, features of bipolar disorder had come to the surface. We faced many difficulties regarding the management of this patient. By this case, the clinicians would have a better understanding of this kind of condition. This report might help clinicians in the management of conversion disorder with comorbid bipolar disorder. Bang J Psychiatry 2022;36(2): 39-41